Cellulose nanofiber derived carbon aerogel with 3D multiscale pore architecture for high-performance supercapacitors. Issue 42 (20th October 2021) - Chen, Lumin; Yu, Houyong; Li, Ziheng; Chen, Xiang; Zhou, Wenlong
Abstract : CNFA assembled supercapacitors exhibit excellent electrochemical performance and demonstrate the feasibility of the practical application. Abstract : Carbon materials are highly promising electrode materials for supercapacitors, due to their hierarchical porous structure and large specific surface area. However, the limited specific capacitance and inferior rate capability significantly prevent their practical application. Herein, 3D interconnected hierarchical porous carbon aerogels (CNFAs) through engineering the pyrolysis chemistry of CNF are developed. The obtained CNFAs effectively improve the carbon yield and suppress the volume shrinkage, as well as have robust mechanical properties. As a supercapacitor electrode, the CNFAs-17% electrode exhibits an ultrahigh capacitance of 440.29 F g −1 at 1 A g −1, significantly superior to most reported biomass-based carbon materials. Moreover, the CNFAs-17% assembled symmetric supercapacitor (SSC) achieves an outstanding rate capability (63.29% at 10 mA cm −2 ), high areal energy density (0.081 mWh cm −2 ), and remarkable cycling stability (nearly 100% capacitance retention after 7000 cycles). This work offers a simple, effective strategy towards the preparation of promising electrode materials for high-performance energy storage applications.